Autism, Equity, and How the Journal Came to Be - Krasnodembski, Megan; Côté, Stephanie; Lai, Jonathan (Canadian Journal of Autism Equity, 2021)
Over the past year a pandemic has swept across the world and, unsurprisingly, revealed gross inequalities across all aspects of life. We saw this in the constant pandemic media coverage that overlooked the experiences of the disability community and, more specifically, the autism community, at least at first. Furthermore, let us not forget in the early days of the pandemic that in countries such as Italy, people without disabilities were prioritized for life-saving machines (Andrews et al., 2020; Lund & Ayers, 2020), contributing to a culture of fear for the one in five Canadians with a disability (Morris et al., 2018) about what would happen to them here. As COVID-19 reached Canadian shores we saw this pattern of inequity quickly replicated within our society. For instance, Canadians with developmental disabilities, such as autism, living in residential settings did not receive the same level of support as those living in different kinds of residences such as retirement residences (Abel & Lai, 2020). Likewise, the initial claims that only people with ‘preexisting conditions’ were at risk implied that those at risk were somehow less valuable to society. Nothing has highlighted the very real problem and extent of ableism within Canadian society as a whole more than these injustices arising from the COVID-19 pandemic, and this is what planted the seed for the Canadian Journal of Autism Equity (CJAE).